2011
DOI: 10.1002/hbm.21314
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiologic correlates of fMRI in human motor cortex

Abstract: Abstract:The neurophysiological underpinnings of functional magnetic resonance imaging (fMRI) are not well understood. To understand the relationship between the fMRI blood oxygen level dependent (BOLD) signal and neurophysiology across large areas of cortex, we compared task related BOLD change during simple finger movement to brain surface electric potentials measured on a similar spatial scale using electrocorticography (ECoG). We found that spectral power increases in high frequencies (65-95 Hz), which hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
177
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 177 publications
(205 citation statements)
references
References 54 publications
22
177
3
Order By: Relevance
“…This remaining saturation in the measured BOLD amplitude in S1 could be explained by neuronal processes that are not captured by the HFB power but by lower frequency bands. 23,41 Although we found a significant decrease in the HFB power for subsequent movements at high movement rates, we observed no movement rate effect for the amplitude in the lower frequency, beta-band power, response (12 to 28 Hz). 17 The beta-band activity, however, remained suppressed between movements at faster movement rates in both motor and sensory cortex, in contrast with the slower movement rates where the beta-band activity recovered to baseline values.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…This remaining saturation in the measured BOLD amplitude in S1 could be explained by neuronal processes that are not captured by the HFB power but by lower frequency bands. 23,41 Although we found a significant decrease in the HFB power for subsequent movements at high movement rates, we observed no movement rate effect for the amplitude in the lower frequency, beta-band power, response (12 to 28 Hz). 17 The beta-band activity, however, remained suppressed between movements at faster movement rates in both motor and sensory cortex, in contrast with the slower movement rates where the beta-band activity recovered to baseline values.…”
Section: Discussioncontrasting
confidence: 71%
“…Studies have shown that power in higher frequencies (440 Hz) correlates well with neuronal firing rates [19][20][21] and also with BOLD signal change. 22,23 The ECoG high-frequency broadband power thus provided a direct measure of electrical activity in confined neuronal ensembles, which we compared with BOLD fMRI measurements. We examined whether addition of the measured neuro-electrophysiological response in a model for the BOLD response affects the mismatch between model-predicted andmeasured BOLD response.…”
Section: Introductionmentioning
confidence: 99%
“…For functional electrode selection and the bulk of analysis reported, we focused on the event-related changes in broad-frequency high γ-power (HG; 70-180 Hz), as used by previous investigators (13,15,16). Changes in power across this frequency range reflect one of the most robust measures of local population activity as recorded by ECoG, particularly given that power in this range is functionally selective, spatially restricted (20), and well-correlated with both population firing rate (17) and fMRI responses (21). Given the RT-based variability of trial duration, we studied both stimulus onset-locked and response-locked data, but focused our quantitative comparisons upon response-locked data, as detailed below (SI Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
“…A wide variety of features in the local field potential (LFP) or EEG, related to several cognitive processes, have now been found to correlate with the BOLD signal (19,20,(22)(23)(24)(25)(26). Most relevant for this study, α-and β-power changes in EEG correlate negatively with the BOLD signal whereas γ-band changes have a positive relation (20,(22)(23)(24)27). Moreover, we and others have demonstrated that neuronal dynamics underlying changes in power in the γ-range contribute independently to the BOLD signal from those in the α-and β-bands (22,27).…”
mentioning
confidence: 99%